The advancements, challenges and future implications of the CRISPR/Cas9 system in swine research - Zhang, J.; Khazalwa, Emmanuel M.; Abkallo, Hussein M.; Zhou, Y.; Nie, X.; Ruan, J.; Zhao, C.; Wang, J.; Xu, J.; Li, X.; Zhao, S.; Zuo, E.; et al. (Elsevier, 2021)
Clustered regularly interspaced short palindromic repeats/CRISPR associated protein 9 (CRISPR/Cas9) genome editing technology has dramatically influenced swine research by enabling the production of high-quality disease-resistant pig breeds, thus improving yields. Additionally, CRISPR/Cas9 has been used extensively in pigs as one of the tools in biomedical research. In this review, we present the advancements of the CRISPR/Cas9 system in swine research such as animal breeding, vaccine development, xenotransplantation, and disease modelling. We also highlight the current challenges and some potential applications of the CRISPR/Cas9 technologies.